Mammal survival at the Cretaceous–Palaeogene boundary: metabolic homeostasis in prolonged tropical hibernation in tenrecs - Lovegrove, Barry G. (The Royal Society, 2014)
Free-ranging common tenrecs, Tenrec ecaudatus, from sub-tropical Madagascar, displayed long-term (nine months) hibernation which lacked any evidence of periodic interbout arousals (IBAs). IBAs are the dominant feature of the mammalian hibernation phenotype and are thought to periodically restore long-term ischaemia damage and/or metabolic imbalances (depletions and accumulations). However, the lack of IBAs in tenrecs suggests no such pathology at hibernation T(b)s > 22°C. The long period of tropical hibernation that we report might explain how the ancestral placental mammal survived the global devastation that drove the dinosaurs and many other vertebrates to extinction at the Cretaceous–Palaeogene boundary following a meteorite impact. The genetics and biochemistry of IBAs are of immense interest to biomedical researchers and space exploration scientists, in the latter case, those envisioning a hibernating state in astronauts for deep space travel. Unravelling the physiological thresholds and temperature dependence of IBAs will provide new impetus to these research quests.